The Sustainability Analysis of Shallot Farming of The Lembah Palu Variety in Sigi Regency - Lien Damayanti; Made Krisna Laksmayani; Shintami Rouwelvia Malik; Mohammad Reyvaldi; Sitti Hardiyanti M.M; Olivia Esther C.R; Mukhlis Mukhlis (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the sustainability of Lembah Palu variety shallot farming in Sigi Regency from economic, social, and environmental perspectives. The research involved 50 shallot farmers selected using a proportional random sampling technique. Primary data were obtained through interviews, field observations, and questionnaires, supported by secondary data from relevant institutions. The sustainability level was assessed using the Multi-Dimensional Scaling (Rapfish) approach to generate sustainability indices for each dimension. The results showed that the overall sustainability status of shallot farming was categorized as less sustainable, with an average index value of 49.37. The environmental dimension recorded the lowest index value (26.97), indicating high vulnerability due to pest and disease intensity, erosion risk, and low utilization of organic inputs. The economic dimension was categorized as fairly sustainable (64.00), as farming activities still provided financial benefits despite high production costs and limited capital access. Meanwhile, the social dimension was also fairly sustainable (57.13), reflecting contributions to household welfare, although farmer institutional strength and land tenure certainty require improvement. Strengthening environmentally friendly practices, improving cost efficiency, and empowering farmer institutions are essential to support balanced and sustainable shallot agribusiness development